Предмет: Алгебра, автор: Bpa42012

(3x/(x^2+2x-1))-(6x/(x^2+3x-1))=5x/(x^2+4x-1)

Ответы

Автор ответа: eugeke
0
 frac{3x}{x^2+2x-1}- frac{6x}{x^2+3x-1} =frac{5x}{x^2+4x-1}\\
 frac{3x}{x^2+2x-1}- frac{6x}{x^2+3x-1} - frac{5x}{x^2+4x-1}=0\\
 frac{3x(x^4+7x^3+10x^2-7x+1)-6x(x^4+6x^3+6x^2-6x+1)-5x(x^4+5x^3+4x^2-5x+1)}{(x^2+2x-1)(x^2+3x-1)(x^2+4x-1)}=0\\
3x^5+21x^4+30x^3-21x^2+3x-6x^5-36x^4-36x^3+36x^2-6x-5x^5-25x^4-20x^3+25x^2-5x=0

-8x^5-40x^4-26x^3+40x^2-8x=0\\
-2x(4x^4+20x^3+13x^2-20x+4)=0\\
-2x^2=0\
x=0\\\
4x^4+20x^3+13x^2-20x+4=0\
(x+2)(4x^3+12x^2-11x+2)=0\
(x+2)(2x-1)(2x^2+7x-2)=0\\
x+2=0\
x=-2\\
2x-1=0\
2x=1\
x= frac{1}{2}\\
<br />2x^2+7x-2=0\
D=49+16=65;  sqrt{D}= sqrt{65}\\
x_{1/2}= frac{-7pm  sqrt{65} }{4}  \\


Ответ: x_1=0;  x_2=-2; x_3= frac{1}{2}; x_4= frac{ sqrt{65} -7}{4}; x_5=  frac{ -sqrt{65} -7}{4}
Похожие вопросы
Предмет: Математика, автор: sultanovakarina58
Предмет: Математика, автор: hdhgdjdvdjb